The role of polyunsaturated fatty acid metabolism in overweight and obese children and adolescents - A. A. Glazyrina (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
The problem of obesity is currently being widely discussed by various specialists. The literature dealing with this problem places a considerable emphasis on investigations of lipid metabolism disorders that occupy a prominent place in the genesis of cardiovascular diseases in the populations of most countries. The special role of long chain polyunsaturated fatty acids that are major functional components of brain membrane structure phospholipids, retinal photoreceptors is emphasized. Pediatricians pay great attention to the nutrition of infants, by adjusting adapted milk-based formulas for their adequate growth and development. At the same time, no consideration is given to the possibility of correcting obesity-associated problems with appropriate adapted milk-based formulas in older infants. However, dietary recommendations for older infants with obesity and overweight should be developed not only in the context of optimization of a qualitative and quantitative diet that ensures the needs of the growing organism at the present moment, but should take into account the prevention of cardiovascular diseases and other complications of obesity in the future.